Critical Art of Teaching Writing: Nepali Educators' Insights into Crafting Young Minds - Khanal, Hota Raj (Education and Development, 2024)
This study is based on the perception and understanding of preprimary level teachers of Nepal. The study was based on the narrative inquiry of the qualitative paradigm. The objective of this study was to explore the freedom in teaching writing to enhance writing skill in preprimary level learners. Based on the objective as well as through the eyes of participants, the collected information was interpreted and concluded that innovative techniques are lacking at preprimary level for effective learning. The study also used social literacy as a lens for the interpretation and description of information to find out the hidden reality. To reveal a method of teaching writing skill, information was collected through in-depth interview with two participants from two different schools selected purposely. Collected information was tabulated, categorized and developed into themes. This study revealed that wall writing, ground writing, and carbon copy symbols techniques are innovative techniques of teaching writing for small children who study at preprimary level and that are incorporated with freedom and natural learning.